Penentuan Utang yang Telah Jatuh Waktu pada Click-Wrap Agreement yang Tidak Mencantumkan Klausul Jatuh Waktu Utang - Louis Alfred Hasudungan; Elisatris Gultom; Nyulistiowati Suryanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Bankcruptcy and Suspension of Payment law is a great solution for debitor who have debt problems with their creditors. Debtors can be declared bankrupt or Suspension of Payment if the debtor is simply proven to have debts to 2 (two) or more creditors and is simply proven to have "a debts that has become due and payableâ€. The existence of "a debts that has become due and payableâ€ is one of the fundamental things in bankruptcy or Suspension of Payment cases. In today's world, determining the existence of â€œa debts that has become due and payableâ€ becomes difficult. The many new forms of agreements and clauses in the world of business law make new difficulties in proving the existence of â€œa debts that has become due and payableâ€ in bankruptcy and Suspension of Payment cases. These difficulties can be found in the click-wrap agreement. Click-wrap agreement is an electronic agreement that uses standard clauses. The unilateral determination of clauses in click-wrap agreements often creates problems in practice. One of the problems that occur is a dispute about the determination of a debts that has become due and payable that comes from the click-wrap agreement between the debtor and the creditor. This is because click-wrap agreement makers often don't specify a debt maturity date in the agreement. Based on the explanation above, this research will examine and analyze the determination of the existence of "a debts that has become due and payable" from click-wrap agreements that do not regulate the debt maturity clause.